Farming, food, and empowerment: The journey of Malawi’s homes industries - Chideya, Yohane; Munthali, Justice; Birachi, Eliud; Rubyogo, Jean Claude (2024)
In 2016, Victoria Mwafulirwa took her first steps into Malawi's small scale agrifood processing landscape. Her venture, Homes Industries, began almost by accident in the northern district of Karonga. After a lucrative catering contract with a local company ended, Mwafulirwa shifted her focus to producing groundnut flour, seizing a market opportunity that has since blossomed into a beacon of hope for thousands of smallholder farmers across Malawi's Karonga, Chitipa, and Nkhata Bay districts.